2019
DOI: 10.1088/1748-9326/ab35be
|View full text |Cite
|
Sign up to set email alerts
|

Evidence, ideology, and the policy of community management in Africa

Abstract: This study examines the performance of the policy of community management for rural groundwater supply in Africa. Across the continent, policies that promote community management have dominated the rural water supply sector for decades. As a result, hundreds of thousands of village-level committees have been formed to manage community boreholes equipped with handpumps. With a significant proportion of these handpumps non-functional at any one time, increasing effort is targeted toward understanding the interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 27 publications
0
24
0
Order By: Relevance
“…Conducting preventative maintenance displayed higher odds of considering affordability and O&M costs than when unconducted. This was expected as affordable maintenance and repair is a crucial factor to ongoing functionality, discussed at length by Whaley et al [65]. There is a risk of preventative maintenance being perceived as a redundant exercise to service providers if a water point is operational [19,57,66] as when water supplies are built correctly they can last for years without issue.…”
Section: Service Delivery-service Providers and Maintenancementioning
confidence: 99%
See 2 more Smart Citations
“…Conducting preventative maintenance displayed higher odds of considering affordability and O&M costs than when unconducted. This was expected as affordable maintenance and repair is a crucial factor to ongoing functionality, discussed at length by Whaley et al [65]. There is a risk of preventative maintenance being perceived as a redundant exercise to service providers if a water point is operational [19,57,66] as when water supplies are built correctly they can last for years without issue.…”
Section: Service Delivery-service Providers and Maintenancementioning
confidence: 99%
“…The revenue collected for the maintenance of assets is crucial towards continued functionality [27,65]. Communities that have available financial resources available are less reliant on external support [65,68].…”
Section: Financial Resources-tariff Frequency Tariff Amount and Usersmentioning
confidence: 99%
See 1 more Smart Citation
“…Community-based management and private utilities have had similar hopes for an improved performance in the past. For instance, the limited ability of community-based management to achieve technical and financial targets has been highlighted in recent years, despite its prevalence in international policy [20][21][22]. Chowns [23] found that maintenance was rarely done, repairs were delayed or sub-standard, and user committees could not save or collect sufficient funds in community-based systems.…”
mentioning
confidence: 99%
“…The underlying capacity of the COWSO to conduct O&M remains a vulnerability to the sustainability of rural water supply, and this is symptomatic of community-based management [18,[44][45][46].…”
mentioning
confidence: 99%